Important Indicators in Increasing Nurse Loyalty in The Covid-19 Pandemic Time - I Wayan Septa Wijaya; Ida Ayu Oka Martini (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Hospital is a means of health efforts that carry out health service activities and is a service provider institution. Health services in a hospital have an important role in achieving success in hospital services. This study aims to determine the effect of intrinsic motivation, leadership, supervision, intrinsic motivation on the satisfaction and loyalty of nurses in Ganesha General Hospital. The number of samples involved was 84 people using random sampling. Data collection was carried out using a questionnaire. Data analysis techniques using smartPLS. The results showed that intrinsic motivation has a positive effect on job satisfaction. Leadership has a positive effect on job satisfaction. Supervision has a positive effect on job satisfaction in nurses. Intrinsic motivation has a positive effect on job loyalty. Supervision has a positive effect on job loyalty. Job satisfaction has a positive effect on job loyalty to nurses at Ganesha General Hospital.